Unpacking Student Entrepreneurial Success: The Strategic Role of Entrepreneurial Character and Organizational Culture - Mulyono, Kemal Budi; Rahman, M. Fathur; Daud, Noorzaidi Mohd (Jurnal Pendidikan Progresif, 2025)
Unpacking Student Entrepreneurial Success: The Strategic Role of Entrepreneurial Character and Organizational Culture. Objective: High entrepreneurial orientation does not guarantee student entrepreneurial success, particularly in Global South contexts, where institutional resource gaps and neglected learning mechanisms often undermine entrepreneurial outcomes. This study fills the gap by integrating the Resource-Based View and Entrepreneurial Learning Theory to explain how entrepreneurial orientation impacts student entrepreneurial success within the Indonesian higher education ecosystems. Method: A quantitative approach, employing a cross-sectional survey design, was utilised, with Likert-scale questionnaires distributed to purposively selected student entrepreneurs. Moderating Partial Least Squares Structural Equation Modeling was applied to analyse data from 180 respondents, examining both direct and moderating effects. Result: The findings show that entrepreneurial orientation has a significant impact on entrepreneurial success, emphasizing the strategic role as a valuable intangible resource.  Among all moderating effects tested, Organizational Culture exerts the most decisive impacts (β = 0.277), compared to Entrepreneurial Characteristics (β = 0.215), underscoring how embedded cultural values critically shape the potency of entrepreneurial orientation on student success. Entrepreneurial characteristics, such as confidence, perseverance, and innovativeness, positively influence outcomes by strengthening entrepreneurial capabilities through learning processes. Organizational culture also emerges as a critical factor shaping entrepreneurial achievements. Notably, interaction effects show that entrepreneurial characteristics and organizational culture significantly moderate the relationship between entrepreneurial orientation and business performance. Conclusion: This study advances theoretical insights by integrating the Resource-Based View and Entrepreneurial Learning Theory. It conceptualises learning as a capability-based mechanism through which internal resources are activated, configured, and deployed, transforming entrepreneurial orientation into actionable competencies that foster student success in constrained institutional settings. This approach offers practical implications for universities seeking to cultivate effective entrepreneurial ecosystems in emerging economies. Keywords: student entrepreneurship, entrepreneurial orientation, organizational culture, emerging economies, higher education, resource-based view, entrepreneurial learning theory.